Droplet‐Based Techniques for Printing of Functional Inks for Flexible Physical Sensors. Issue 20 (26th March 2021) - Abdolmaleki, Hamed; Kidmose, Preben; Agarwala, Shweta
Abstract: Printed electronics (PE) is an emerging technology that uses functional inks to print electrical components and circuits on variety of substrates. This technology has opened up new possibilities to fabricate flexible, bendable, and form‐fitting devices at low‐cost and fast speed. There are different printing technologies in use, among which droplet‐based techniques are of great interest as they provide the possibility of printing computer‐controlled design patterns with high resolution, and greater production flexibility. Nanomaterial inks form the heart of this technology, enabling different functionalities. To this end, intensive research has been carried out on formulating inks with conductive, semiconductive, magnetic, piezoresistive, and piezoelectric properties. Here, a detailed landscape view on different droplet‐based printing technologies (inkjet, aerosol jet, and electrohydrodynamic jet) is provided, with comprehensive discussion on their working principals. This is followed by a detailed research overview of different functional inks (metal, carbon, polymer, and ceramic). Different sintering methods and common substrates being used in printed electronics are also discussed, followed by an in‐depth review of different physical sensors fabricated by droplet‐based techniques. Finally, the challenges facing the field are considered and a perspective on possible ways to overcome them is provided. Abstract : Three types of droplet‐based printing techniques, namely inkjet, aerosol jet, and E‐jet, are reviewed in depth. Furthermore, other important aspects of printed electronics such as functional inks, sintering methods, and flexible substrates are thoroughly discussed. Finally, the physical sensors fabricated by droplet‐based techniques, and main challenges toward printed electronics are also reviewed.